HEAT TRANSFER IN MULTI-CONNECTED AND IRREGULAR DOMAINS WITH NON-UNIFORM MESHES - Romão, E. C.; Aparecido, J. B.; Campos-Silva, J. B.; Moura, L. F. M. (Revista de Engenharia Térmica, 2008)
In this work is presented a numerical solution for temperature profile in two-dimensional diffusion inside irregular multi-connected geometry. The special discretization has been done by two variants of the finite Element Method: Galerkin Finite Element Method (GFEM) and Least Squares Finite Element Method (LSFEM). Three applications are presented. The first for a regular double connected domain; the second for a regular multi-connected domain and the third application for an irregular multi-connected domain. In all applications are considered Dirichlet boundary conditions. The results obtained in the present work are compared with results from Ansys® simulations. The results of each method are presented and discussed and the characteristics and advantages of the methods are also discussed.